Studi Komparasi Motivasi Belajar Kimia Siswa Kelas X Program Peminatan dan Lintas Minat di MAN 2 Kota Bengkulu - Elinge Haster; Salastri Rohiat; Sumpono Sumpono (ALOTROP, 2019)
The purpose of this research was to measure differences chemistry learning motivation of tenth grade students class at major (MIPA) and cross-major (IPS) courses in MAN 2 Bengkulu city. The population in this research is 260 students from 8 classes consisting of four MIPA classes and four IPS classes and also become sample in this research. The type of this research is quantitative descriptive that aims to provide a description of the variables of learning chemistry motivation in the class of major (MIPA) and cross-major (IPS) and emphasize the analysis on data figures obtained by statistical methods. Chemical learning motivation data obtained from the results of a questionnaire motivation to learn chemistry. Questionnaire of motivation to learn chemistry consists of 61 items that validity tested by using SPSS (Statistical Package for the Social Sciences) program to obtain 54 valid items and 7 invalid items and tested reliability with Cronbach's Alpha value of 0.897 and this questionnaire is stated reliable. The research questionnaires were analyzed using normality test, homogeneity test and hypothesis test. The average value of students' learning motivation of major (MIPA) and cross-major (IPS) in chemistry subjects was 197.19 and 189.71 in the good category. The hypothesis testing by using the test T 0.05 at significant level, then it was gained value namely 2.8027 > 1.6508. The results showed that there is a significant difference between major courses and cross-major courses in the chemistry learning motivation of tenth grade students. Motivation to learn chemistry in the major courses better than cross-major courses.